Selection of Construction Bidders Using the Analytical Hierarchy Process and Friedman Theory - Salman, Alaa (Frontiers in Built Environment, 2022)
Selecting a suitable bidder to execute a construction project is not an easy task, especially for the short bidder list. The consequences of the selection might affect the project performance in terms of cost, money, and quality. The current research in this paper deals with the selection of a contractor, who bids on a specific project. The historical data of contractors is a key of the selection based on three approaches: quick selection approach (QSA), generic selection approach (GSA), and comprehensive selection approach (CSA). QSA relies on the scoring system according to delay factors. QSA is the weighted average of the delay factors using the Analytical Hierarchy Process (AHP), CSA is based on the integrated QSA and the bidding strategy using Friedman’s theory. The current three approaches can be utilized by public and private owners, who intend to select a general contractor to execute new construction projects. A hypothetical case study is implemented to demonstrate the developed models. Several experts in the field of construction management have confirmed the findings. The third strategy (CSA) is found to be the most appropriate for selecting construction bidders.